2019
DOI: 10.1002/adem.201900089
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Forming of Al‐Mg Alloy Sheet for Car Outer Body Applications

Abstract: During deep‐drawing of Al‐Mg sheet at room temperature, stretcher‐strain marks can appear on the material's surface. Such parts are not suitable for car outer body applications because the visually unappealing marks are still visible after painting. In this paper, the occurrence of surface marks on a miniaturized engine hood is significantly reduced by deep‐drawing at approximately −180 °C. Yield strength, ultimate tensile strength, and tensile elongation are significantly higher at cryogenic temperature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Recent studies show the advantages of deformation at sub-zero temperatures [16][17][18][19][20][21][22][23][24]. Schneider et al [18] described an increase in uniform elongation of 75% for the Al-Mg alloy EN AW 5182 when the temperature is lowered to 77 K. In a multiaxial stress state, realized by limiting dome height experiments, a significant improvement was also achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show the advantages of deformation at sub-zero temperatures [16][17][18][19][20][21][22][23][24]. Schneider et al [18] described an increase in uniform elongation of 75% for the Al-Mg alloy EN AW 5182 when the temperature is lowered to 77 K. In a multiaxial stress state, realized by limiting dome height experiments, a significant improvement was also achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Readers are invited to refer to the following studies for in-depth insights into the other cold forming processes itemized above. [58][59][60][61][62][63][64][65][66][67] Several experimental and theoretical studies have been carried out to assess the potential of WT forming for the production of industrial parts from precipitation-hardenable aluminum alloys. In another study, [57] for example, WT forming was compared to cold forming in the T6 condition in the precipitation-hardenable aluminum alloy AA7075 by forming an automotive B-pillar using an industrial tool.…”
Section: Cold Forming Of Aluminummentioning
confidence: 99%
“…Readers are invited to refer to the following studies for in‐depth insights into the other cold forming processes itemized above. [ 58–67 ]…”
Section: Forming Strategies To Overcome the Forming Limit Of Aluminum...mentioning
confidence: 99%
“…A combination of high strength and good ductility was achieved for the alloy. Grabner et al [ 88 ] used deep‐drawing at ≈93 K to produce Al–Mg alloy outer body car parts and found that deep‐drawing at 93 K was effective in reducing stretcher‐strain marks. As shown in Figure , the RT‐formed part has an average waviness of 5 μm, while the cryo‐formed one shows no sign of waviness.…”
Section: Cryo‐forming Techniquesmentioning
confidence: 99%